Personalized lung-protective ventilation in children - Is it possible? - Shekhar T Venkataraman (Wolters Kluwer Medknow Publications, 2023)
Mechanical ventilation, while life-saving, can be associated with risks of exacerbating existing lung injury or causing new injury. An understanding of how mechanical ventilation can injure the lung and other systems is important to develop an optimal ventilatory approach. Over the past 70 years, different mechanisms that can cause lung injury have been described with putative suggestions for lung protection. Which mechanisms are operating in a particular patient is difficult to ascertain at the bedside. Guidelines have been formulated for both adults and children for the management of patients on mechanical ventilation with acute respiratory distress syndrome. Lung protection is the main objective of these guidelines. Lung disease is not homogeneous within the lung, and between patients with the same diagnosis. Response to ventilatory parameters also differs based on the distribution of injured and uninjured lungs, being beneficial in some but harmful in others. The impact of mechanical ventilation on the cardiovascular system and other systems is also variable. It is important to understand that these guidelines are one-size-fits-all therapeutic suggestions. While guidelines are useful, it is important to personalize mechanical ventilation based on the patient's lung mechanics and their response to adjustments of the ventilatory parameters. This chapter will review the current knowledge of the factors that contribute to injury to the lungs from mechanical ventilation. At the end of the review, I have formulated a personalized approach to lung protection during invasive mechanical ventilation for patients with parenchymal lung disease - a consensus of one.